2017
DOI: 10.1253/circj.cj-16-0958
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiovascular Responses to Alamandine in Two-Kidney, One Clip Hypertensive and Normotensive Rats

Abstract: angiotensin II type 1 receptor (AT1R) blockers. These drugs block angiotensin II (Ang II) -the primary active peptide in the RAS, which has many effects on blood vessels, the heart, the brain and the kidneys -from activating AT1R. AT1R is one of the two well-characterized receptors that Ang II activates (in addition to angiotensin II type 2 receptor (AT2R)). 3 Losartan is an angiotensin receptor blocker, 4 which mainly antagonizes AT1R, while PD123319 can block AT2R and Mas-related G protein-coupled receptor D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…An LVEDP level >16 mmHg has been considered to be a sign of left ventricular diastolic dysfunction. 20) Alamandine decreased LVEDP in hypertensive rats which is most likely a result of improved cardiac function after alamandine using. Improvement in heart function and cardiomyocyte hypertrophy was seen in Ang-(1-7)-treated mice.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An LVEDP level >16 mmHg has been considered to be a sign of left ventricular diastolic dysfunction. 20) Alamandine decreased LVEDP in hypertensive rats which is most likely a result of improved cardiac function after alamandine using. Improvement in heart function and cardiomyocyte hypertrophy was seen in Ang-(1-7)-treated mice.…”
Section: Discussionmentioning
confidence: 93%
“…9) Ang A can be hydrolyzed by ACE2 to generate alamandine, and alamandine can also be produced directly from Ang (1-7) by decarboxylation of its aspartate residue. 10) Alamandine and Ang (1-7) are also structurally similar; the only difference between these 2 peptides is the presence of alanine (in alamandine) in place of an aspartate residue in the amino terminus. They have similarity in most of their biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ang 1-7 induces vasodilator, natriuretic, and diuretic effects through the mas receptor. It has been suggested that alamandine, a heptapeptide with an Ang1-7-like structure, exhibits actions similar to Ang1-7 [5,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, mean arterial pressure and left ventricular sys tolic pressure increased briefly in an AT 1 R dependent manner, followed by a reduction in these parameters, which persisted throughout the rest of the infusion period. This anti hypertensive effect was reversed by PD123319, an AT 2 R antagonist 68 . Additionally, alaman dine treatment mitigated vascular remodelling in mice subjected to transverse aortic constriction 69 .…”
Section: Systemic Hypertension and Remodellingmentioning
confidence: 95%